Climate warming is expanding dengue burden in the Americas and Asia - Marissa L. Childs; Kelsey Lyberger; Mallory J. Harris; Marshall Burke; Erin A. Mordecai (Proceedings of the National Academy of Sciences, 2025)
Climate change is expected to pose significant threats to public health, particularly vector-borne diseases. Despite dramatic recent increases in dengue that many anecdotally connect with climate change, the effect of anthropogenic climate change on dengue remains poorly quantified. To assess this link, we assembled local-level data on dengue across 21 countries in Asia and the Americas. We found a nonlinear relationship between temperature and dengue incidence with the largest impact of warming at lower temperatures, peak incidence at 27.8°C, and a decline at higher temperatures. Using this inferred temperature response, we estimate 18% (95% CI: 11 to 27%) of historical dengue incidence on average across our study countries is attributable to anthropogenic warming. Future warming could further increase incidence by 49% (95% CI: 16 to 136%) to 76% (95% CI: 27 to 239%) by midcentury for low or high emissions scenarios, respectively, with cooler regions projected to double in incidence due to warming while other currently hot regions experience little impact or even small declines. Under the highest emissions scenario, we estimate that 262 million people are currently living in places in these 21 countries where dengue incidence is expected to more than double due to climate change by midcentury. These insights highlight the major impacts of anthropogenic warming on dengue burden across most of its endemic range, providing a foundation for public health planning and the development of strategies to mitigate future risks due to climate change.